Energy, economic, and environmental analysis of a flat-plate solar collector operated with SiO2 nanofluid - Faizal, M.; Saidur, Rahman; Mekhilef, Saad; Hepbasli, A.; Mahbubul, I.M. (2015)
To overcome the environmental impact and declining source of fossil fuels, renewable energy sources need to meet the increasing demand of energy. Solar thermal energy is clean and infinite, suitable to be a good replacement for fossil fuel. However, the current solar technology is still expensive and low in efficiency. One of the effective ways of increasing the efficiency of solar collector is to utilize high thermal conductivity fluid known as nanofluid. This research analyzes the impact on the performance, fluid flow, heat transfer, economic, and environment of a flat-plate solar thermal collector by using silicon dioxide nanofluid as absorbing medium. The analysis is based on different volume flow rates and varying nanoparticles volume fractions. The study has indicated that nanofluids containing small amount of nanoparticles have higher heat transfer coefficient and also higher energy and exergy efficiency than base fluids. The measured viscosity of nanofluids is higher than water but it gives negligible effect on pressure drop and pumping power. Using SiO2 nanofluid in solar collector could also save 280 MJ more embodied energy, offsetting 170 kg less CO2 emissions and having a faster payback period of 0.12 years compared to conventional water-based solar collectors.